Gangguan Sistem Penglihatan pada Pasien Pre-eklampsia/Eklampsia: Tinjauan Pustaka - Ekaputri, Maria Vania Tri (PT Kalbe Farma Tbk., 2025)
Pre-eclampsia and eclampsia are constrictive vasculopathy diseases which may involve retina, retinal blood vessels, and brain cortex, causing mild to severe visual complications and even blindness. These problems can be prevented with regular early detection or comprehensive examination. Appropriate and fast treatment can reduce the risk of more severe damage and even permanent disability.